Age, growth and otolith morphometry of Atlantic bonito (Sarda sarda Block, 1793) from the eastern Mediterranean Sea - Kotsiri, Mado (Array, 2018)
The otoliths of the Atlantic bonito, Sarda sarda (Bloch, 1793), were examined with the aim to estimate the age and growth of the species in the eastern Mediterranean Sea and to reveal possible relationships between otolith shape or size and age. All specimens used in this study, ranging from 7.2 to 70.4 cm in fork length and from 20 to 4889 g in total weight, were caught in the Aegean and Ionian Seas during the period 1997-2010. Otolith morphometry was studied using image analysis techniques for all intact sagittae ranging in weight from 0.6 to 11.3 mg and four shape indices were calculated. No statistical significant differences between left and right otolith morphometric variables were found. The age of fish was estimated by counting the pairs of opaque and translucent bands in transversal thin sections of otoliths. The estimated ages ranged from 0+ to 7 years and the von Bertalanffy growth parameters were determined \((L∞=79.9 cm, k=0.261 and to=-1.230 years)\). The examination of the type of growth bands at the outside margin of each otolith per month showed that one translucent band is formed annually during the cold season. The results revealed statistically significant relationships between otolith morphometric variables and fish length or age. Among the variables, otolith weight was the one that showed the highest correlation with age (R=0.77). Therefore, otolith weight could represent a valuable criterion for age estimation in Atlantic bonito that is objective, economic and easy to perform compared to annuli counting method in hard parts.